Contributions from Buberian anthropology to studies on disability - Zárate Flores, Paola (2017)
The trial presented below aims to provide a new approach to disability issues, taking into consideration as first ethical value and recognition of the human phenomenon. The study of Man, from the anthropological-philosophical view of author Martin Buber, promotes an understanding of the phenomenon from a vision of totality, where the introduction of concepts such as comparison, differentiation, subjectivity and essential relationship favoring re-significance of the subject, from the development of some considerations that try to revitalize the many qualities and possibilities of man, from an intersubjective and contemplative look the same, which is established from the existence of the essential I-Thou relationship.